90-Day Specific Readmission for Clostridium difficile Infection After Hospitalization With an Inflammatory Bowel Disease Flare: Outcomes and Risk Factors. Issue 4 (19th August 2020) - Palacios Argueta, Pedro; Salazar, Miguel; Attar, Bashar; Simons-Linares, Roberto; Shen, Bo
Abstract: Background: Patients with inflammatory bowel disease (IBD) have an increased risk for Clostridium difficile infection (CDI) and carry significantly higher morbidities and mortality than those without IBD. We aimed to investigate disease-specific readmission rates and independent risk factors for CDI within 90 days of an index hospitalization for an IBD flare. Methods: The Nationwide Readmission Database was queried for the year 2016. We collected data on hospital readmissions of 50, 799 adults who were hospitalized for urgent IBD flare and discharged. The primary outcome was disease-specific readmission rate for CDI within 90 days of discharge. The secondary outcomes were readmission rate of colonoscopic procedures, morbidities (including mechanical ventilation and shock), and hospital economic burden. The risk factors for readmission were identified using Cox regression analysis. Results: The 90-day specific readmission rate was 0.1% (N = 477). A total of 3, 005 days were associated with readmission, and the total health care in-hospital economic burden of readmission was $19.1 million (in charges) and $4.79 million (in costs). Independent predictors during index admission for readmission were mechanical ventilation for >24 hours (hazard ratio [HR], 6.62, 95% confidence interval [CI], 0.80-54.57); history of previous CDI (HR, 5.48; 95% CI, 3.66-8.19); HIV-positive status (HR, 4.60; 95% CI, 1.03-20.50); alcohol abuse disorders (HR, 2.06; 95% CI, 1.15-3.70); Parkinson's disease (HR, 4.68; 95% CI, 1.65-13.31); index admission for noncomplicated ulcerative colitis (HR, 4.72; 95% CI, 2.99-7.45]-), complicated ulcerative colitis (HR, 4.49; 95% CI, 2.80- 7.18), or noncomplicated Crohn disease (HR, 2.54; 95% CI, 2.80-4.04); and hospital length of stay (HR, 1.01; 95% CI, 1.01-1.02). Conclusions: The 90-day CDI-specific readmission rate after the index admission of IBD flares was 0.1%. We found risk factors for CDI-associated readmissions such as history of Parkinson's disease, prior CDI, HIV-positive status, and alcohol abuse disorder. Finally, our study also revealed a high health care cost, charges, and burden.